2021
DOI: 10.1111/jasp.12740
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mortality reminders on cultural in‐group versus out‐group takeaway food safety perceptions during the COVID‐19 pandemic

Abstract: During the early stages of the COVID‐19 pandemic takeaway food orders generally increased, yet sales of Chinese and Italian food declined. At this time, news sources ran stories on the safety of cuisine from these countries, frequently juxtaposed with communications on mortality‐related information related to the virus. Terror management theory suggests mortality concerns can lead people to defend against the psychological threat of death by bolstering positive evaluations of products and values of their own c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Therefore, to avoid differential treatment by those around them, such as being talked about or avoided, individuals exposed to SARS‐CoV‐2 may focus on maintaining their own image in the minds of others, thereby triggering their defensive impression management motivation. Some studies have demonstrated that the anxiety of potential separation from those around them motivates individuals to protect their self‐esteem during the COVID‐19 pandemic (McCabe & Erdem, 2021 ; Steele, 2020 ). Thus, we proposed the following hypothesis:…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Therefore, to avoid differential treatment by those around them, such as being talked about or avoided, individuals exposed to SARS‐CoV‐2 may focus on maintaining their own image in the minds of others, thereby triggering their defensive impression management motivation. Some studies have demonstrated that the anxiety of potential separation from those around them motivates individuals to protect their self‐esteem during the COVID‐19 pandemic (McCabe & Erdem, 2021 ; Steele, 2020 ). Thus, we proposed the following hypothesis:…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…It is not constructive to be alarmist about the challenge's globalization poses for food safety, nor to leave the suggestion that globalization is a force which should be resisted to prevent pandemics of this nature (McCabe and Erdem, 2021). The World Health Organization recognizes several significant benefits which are afforded to nations that are integrated into the global food trade.…”
Section: Globalization Food and Covid-19mentioning
confidence: 99%
“…Moreover, uptake of recommended personal hygiene behaviors such as wearing masks and frequent handwashing is a key factor in the control of this highly transmissible virus. Bringing one’s own eating utensils when dining out and the use of serving utensils for shared dishes have also been shown to be effective in reducing transmission [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. To control the local outbreak, the Hong Kong health authorities and public health experts (a) promptly implemented a series of non-pharmaceutical measures including school closure, work from home arrangement for civil servants, reduced restaurant hours and closure of bars [ 23 ]; (b) actively recommended mask use and frequent hand sanitation very early in the pandemic [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%